Strengthening Strategy and Results Framework through Prioritization - CGIAR Independent Science and Partnership Council (CGIAR Independent Science and Partnership Council, 2012)
This report examines processes and methods for priority setting to underpin a future revision of the SRF by the Consortium. This paper examines priority setting at both the strategic System level (SRF/SLOs) and at the operational level of CGIAR research programs.